Improving Students’ Vocabulary Mastery Through Learning At Madrasah Aliyah Yadi Funju - Taufan, Muhammad Ybnu; Aras, Muhammad Sahrir (AhInstitute of Research and Community Service (LP2M) Institute of Social Sciences and Business Andi Sapada, 2025)
The researcher found that there were still many students who felt bored while learning and had difficulties in memorizing vocabulary. The research methods used are Classroom Action Research (CAR). The population in this research were all students at MA Yadi Cabang Funju, and the sample was the x grade students of MA yadi Cabang Funju with a total of 15 people. Three instruments were used in this research, interview guideline, observation, and questionnaire. In addition, there are four data analyses in this research, namely data collection, data reduction, data presentation, and drawing conclusions. The result of this research that in cycle I, there was 1 student with a percentage 50-69% are in the fair category. And a total 14 students with a percentage 0-49% are in the poor category. In cycles II as many as 7 students with above average ability with a percentage of 70-89% are in the good category. A total of 6 students with average ability with a percentage of 50-69% are in enough category, and 2 students with below average ability with a percentage of 0-49% are in the not enough category. From this result, it can be concluded that students experienced a 50-69% increase vocabulary through outdoor learning,